Predictors of HIV testing adherence among men who have sex with men: a cross-sectional study - Laelson Rochelle Milanês Sousa; Raphael Augusto Gir de Carvalho; Daniel de Macêdo Rocha; Marcela Antonini; Milton Jorge de Carvalho Filho; Maria Wiklander; Elucir Gir; Renata Karina Reis (BMC Public Health)
Abstract Men who have sex with men are a target group for HIV prevention and control. HIV testing is part of a broader combination prevention strategy. This study aimed to analyze the predictors for adherence to HIV infection testing among Brazilian men who have sex with men. A cross-sectional study was conducted with 1438 participants, online selected for convenience in all regions of Brazil. Binary logistic regression analysis was used to identify independent predictors of HIV testing in the study population. Adherence to the HIV test was high (80.1%). Had condomless anal intercourse in the last 12 months (Adjusted Odds Ratio [AOR]: 1,659; 95% Confidence Interval [CI]:1,12 − 2,43; p = 0,010), knew one place to seek HIV testing (AOR 6,158 [IC95%: 4,27 − 8,86]; p < 0,001), Received counselling on HIV testing by a health professional (AOR 3,389 [IC95%: 2,28 − 5,02]; p < 0,001), Have been diagnosed with STI (AOR 2,266 [IC95%: 1,41 − 3,62]; p < 0,001) and Knew someone living with HIV (AOR 1,86 [IC95%: 1,29 − 2,67]; p < 0,001) were independently associated with higher chances of HIV testing.